Evaluating the effectiveness on BIM training programme in proposing guideline at myBIM centre, Malaysia / Muhammad Fakar Badrul Hisham - Badrul Hisham, Muhammad Fakar (2022)
BIM is now one of the technologies used in the construction industry. The Malaysian government has promoted the use of BIM since 2013 through CIDB, and different studies have shown that BIM adoption in the construction industry offers several benefits and challenges for construction stakeholders. CIDB Malaysia has recognised myBIM Centre as a certified BIM training provider in Malaysia. Numerous individuals and organisations have seen the advantages of BIM training and participate actively. But, the main problem, is how to measure the effectiveness of the training, in addition, myBIM Centre is a new development and the existing evaluation is for the moderate only not reflect the performance outcomes of the trainee. Therefore, the purpose of this research is to enhance BIM training programme based on attitude, knowledge and skill development in proposing guidelines at myBIM Centre. The objective is to identify the effect of demographic background on the training, to examine the effectiveness of attitude, knowledge and skill development towards performance indicators and to propose a guideline for enhancement of BIM training programme. The primary data were collected from the questionnaire survey.